2022
DOI: 10.3389/fmolb.2022.871737
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of RNA Modification in Mouse Germ Cell-2 Spermatids Under Hypoxic Stress

Abstract: Hypoxia is a known stress factor in mammals and has been shown to potentially impair male fertility, which manifests as spermatogenic dysfunction and decreased semen quality. Studies have shown that RNA modifications, the novel post-transcriptional regulators, are involved in spermatogenesis, and hypoxia-induced alterations in RNA modification in testes and sperm cells may be associated with impaired spermatogenesis in mice. However, the molecular mechanisms via which RNA modifications influence spermatogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The quantity of KIF2C within the sperm is closely associated with fertilization and the early stages of embryogenesis. Animal experiments demonstrated the importance of KIF2C in spermatic mitosis and meiosis ( He T. et al, 2022 ). We found that environmental stimuli upregulate KIF2C in elongated spermatids, thereby influencing spermatic mitosis and normal sperm cell development.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of KIF2C within the sperm is closely associated with fertilization and the early stages of embryogenesis. Animal experiments demonstrated the importance of KIF2C in spermatic mitosis and meiosis ( He T. et al, 2022 ). We found that environmental stimuli upregulate KIF2C in elongated spermatids, thereby influencing spermatic mitosis and normal sperm cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blotting was performed to evaluate tRNA expression levels in the mouse liver during T. gondii infection as previously described [ 29 ]. Total RNA was separated on a 15% urea-PAGE gel.…”
Section: Methodsmentioning
confidence: 99%
“…(4) Although tsRNAs exist in serum, plasma, saliva, and urine, tsRNAs themselves have many modifications [ 135 ]. The stability of tsRNAs, their capacity to be recognized through RNase, and ultimately their ability to generate tsRNAs are all impacted by these alterations, which considerably affect the structure and function of tsRNAs [ 136 ]. Therefore, whether the different types of tsRNAs produced at different sites can be stably expressed in exosomes as biomarkers still needs to be verified in many investigations.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%